Spousal Influence on Early Retirement Behavior - Zhiyang Jia (Statistics Norway, Research Department, 2005)
In this paper, we use a binary choice panel data model to analyze married individuals.retirement behavior in Norway when a new option, AFP early retirement becomes available. We focus our study on the influence of the spouse.s characteristics on early retirement behavior. We find the directions of spousal eects are quite symmetric but women seem to have a much stronger response to their spouses' characteristics than men. The comparison of dierent specifications indicates that correct modeling of the error term covariance structure in a panel data binary choice model is quite important.
Keywords: H55; J26; 330; Retirement; Spousal Influence; Panel Data; Random Effects.